KARAKTERISTIK AUDITEE DAN AUDITOR TERHADAP AUDIT DELAY PADA PERUSAHAAN DI BEI PERIODE 2013-2017 - ULFAH, ISMIATI; NYOMAN ALIT TRIANI, NI (Jurnal Akuntansi AKUNESA, 2020)
ABSTRACT This paper empirically analyzes the effect of auditee and auditor characteristics on audit delay. Specifically, auditee characteristics used are profitability, solvability, and company size while auditor characteristics used are audit-firm size, auditor opinion, and audit tenure. This research was conducted on trade, services, and investment sector in 2013-2017 and produced 370 samples which are chosen by using purposive sampling. The technique analysis used is multiple regression analysis. The results of the study indicate that profitability and auditor opinion has a positive effect on audit delay while audit-firm size has a negative effect on audit delay. Whereas solvability, company size, and audit tenure has not a significant effect on audit delay. Keywords: Audit Delay; Auditee Characteristics; Auditor Characteristics.